THE IMPACT OF THE CONSISTENCY IN THE TEXTUAL COHERENCE IN THE STORYOF (HAY BIN YAQDHAN) - Dr. Sadeeq Battal Houran Salih (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper is interested in an important aspect of the Andulsi prose namely the literary aspect since it studies a literary message which is the message of Ibn Tufail entitled (Hay Bin Yaqdhan) and we tried by this study to concentrate on the elements of the consistent creativity and its impact in the textual coherence through functioning some things like preceding reference, subsequent reference and repetition.